Phase and morphology controlled in the synthesis of iron oxide particles: dimension-based carbonaceous materials as modifiers. Issue 85 (30th August 2016) - Huang, Qitong; Zou, Liling; Chen, Dejian
Abstract : Different phases and morphologies of iron oxide were selectively synthesized in the presence of different dimension carbonaceous materials as modifiers. Abstract : Different phases and morphologies of iron oxide and its hybrid nanomaterials can be selectively synthesized by a hydrothermal process in the presence of different dimension carbonaceous material modifiers. This opens up a new method for directly controlled synthesis of metal oxides and their hybrids with carbonaceous materials.